Исследование динамики гидравлического сопротивления конденсаторов в системах технического диагностирования - Шелепов, И. Г.; Сафронюк, М. А. (НТУ "ХПИ", 2009)
Diagnostics of vacuum in condensers in the course of electric power generation is one of actual tasks during power units maintenance. The possibility of the technical diagnostics perfection of the current vacuum of a condenser due to the more precise definition of the thermal resistance value is proposed
Keywords: потери напора; численный анализ; экосистемы; водоемы-охладители